Multimedia for Cultural Heritage First International Workshop, MM4CH 2011, Modena, Italy, May 3, 2011, Revised Selected Papers - Grana, Costantino; Cucchiara, Rita.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the revised selected papers from the First International Workshop on Multimedia for Cultural Heritage, MM4CH 2011, held in Modena, Italy, on May 3, 2011. The 8 full papers and 9 poster papers included in this volume were carefully reviewed and selected from 25 submissions. In addition, the book contains a paper resuming the outcome of the discussion session. The workshop aimed on creating a profitable informal working day to discuss hot topics in multimedia, with special application to cultural heritage. The papers of the oral session are divided in topical sections named interaction and analysis and management.
Keywords: Computer science; Computer communication systems; Information storage and retrieval; Multimedia information systems; User interfaces (Computer systems).; Artificial intelligence; Image processing; Computer Science; Multimedia Information Systems; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Image Processing and Computer Vision; Computer Communication Networks; Information Storage and Retrieval; Electronic books